Immunosuppressive Potential of Activated Human Amniotic Cells in an Experimental Murine Model of Skin Allo- and Xenotransplantation - Kolanko, Emanuel; Grajoszek, Aniela; Czekaj, Piotr (Frontiers in Medicine, 2021)
Isolated human amniotic cells (hAC) could be used as a source of immunomodulatory factors in regenerative medicine and transplantation. However, in previous experimental studies, native hAC administered to skin graft recipients did not induce graft immunotolerance. To strengthen the immunomodulatory properties of hAC prior to administration to the recipient, we activated them ex vivo using pro inflammatory cytokines. In this study, we compared the transplantation efficiency of skin allografts and xenografts in mice treated with Cyclosporine A (CsA) (10 or 50 mg/kg body weight (bw)) and hAC activated ex vivo by IL-1β and INFγ, administered to the tail vein or subcutaneously. During 15 days of observation, hAC administered intravenously or subcutaneously after allotransplantation appeared to be as safe and efficient as CsA at the dose of 10 mg/kg bw in preventing rejection of skin allo- and xenografts. After xenotransplantation, however, only hAC administered intravenously prevented rejection to an extent comparable to CsA. Both CsA (10 mg/kg bw) and activated hAC reduced inflammatory infiltration in the skin (after intravenous injection) and did not increase the concentration of the inflammation marker SAP in serum or percentage of leukocytes in blood. Finally, we concluded that administration of activated hAC is safe and efficient in the presented animal model of skin allo- and xenotransplantation in a route-dependent manner. Activated hAC injected intravenously exhibit an immunosuppressive effect comparable to CsA administered at the dose of 10 mg/kg bw in both allo- and xenotransplantation.